What causes asymmetric price transmission in agro-food sector? Meta-analysis perspective - Zoltán Bakucs; Jan Fałkowski; Imre Fertő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
There now exists a large literature on price transmission in agro-food sectors. However, a great majority of empirical studies focus on the existence of asymmetry and, by and large, do not allow investigating the reason for its presence or absence. This is in sharp contrast to the theoretical literature that provides a number of explanations for why we should expect (a)symmetry. In response to this, this paper tries to uncover the reasons for asymmetric price transmission in the agro-food chain. To do so, we use meta-analysis drawing on the existing studies from this area. Our focus is on the organizational and institutional characteristics of the agro-food supply chain. Our findings suggest that asymmetric price transmission in farm-retail relationship is more likely to occur in sectors/countries with more fragmented farm structure, higher governmental support and more restrictive regulations on price controls in retail sector. On the other hand, more restrictive regulations on entry barriers in retail sector and relative importance of the sector in question tend to promote symmetric farm-retail price transmission. The latter is also more likely in the presence of strong processing industry.
Keywords: Q11; 330; price transmission; meta-regression analysis; agro-food supply chain; Geldpolitische Transmission; Agrarpreis; Lieferkette; Agroindustrie; Meta-Analyse